UNVEILING THE HISTORY OF NAHWU SCIENCE IN IRAQ - Mahdi, Muhammad; Ulfatuh Hasanah (Triwikrama: Jurnal Ilmu Sosial, 2025)
This research discusses the history of Nahwu in Iraq with the development of correlation and implementation of valid data. Iraq was the earliest region to contribute to the science of nahwu. This research uses a qualitative method. The data collection technique used is a literature study, where the data listed are obtained from books, journals and other secondary references and then implement the relevant data to examine the history of Imu Nahwu in Iraq. The results showed that in its history the forerunner of nahwu science emerged because of the many phenomena of lahn errors in the Arab community. The first laying of the foundation of the science of nahwu was in Bashrah precisely in Iraq by Abul Aswad Da-Duali who had previously been authorized by the caliph Ali bin Abi thalib. As time passed, the thought of nahwu science grew and gave rise to schools of nahwu which also gave birth to generations of nahwu intellectuals.